PERBANDINGAN PENGUASAAN KONSEP TERMOKIMIA MODEL LC 6 PHASE DENGAN LC 3 PHASE - Yani Efrina; Tasviri Efkar; Lisa Tania (Universitas Lampung, 2013)
The purpose of research was to find out the mastering comparison of thermochemical concept between learning cycle 6 phase model and learning cycle 3 phase model at MAN Krui Kabupaten Pesisir Barat. The population in this research is all of XI grade science students in academic year 2012/2013. Samples was taken by using purvosive sampling technique. We got class XI IPA1 as a class experiment 1 and XI IPA2 as a class experiment 2. This research used non-equivalent pretest posttest control group design. The result of this research showed that there is a difference in score average of mastering thermochemical concept between learning cycle 6 phase model and learning cycle 3 phase model. The average of thermochemical concept mastering by implementing learning cycle 6 phase model is higher than learning cycle 3 phase model, because learning cycle 6 phase model has more detail steps to improve the thermochemical concept mastering.Tujuan penelitian adalah untuk mengetahui perbandingan penguasaan konsep termokimia antara model learning cycle 6 phase dengan learning cycle 3 phase pada siswa MAN Krui Kabupaten Pesisir Barat. Populasi dalam penelitian adalah semua siswa kelas XI IPA tahun ajaran 2012/2013. Sampel diambil menggunakan teknik purposive sampling. Diperoleh kelas XI IPA1 sebagai kelas eksperimen I dan kelas XI IPA2 sebgai kelas eksperimen II. Penelitian menggunakan rancangan non-equivalent pretest posttest control group design. Hasil dari penelitian terdapat perbedaan rata-rata nilai penguasaan konsep termokimia antara model learning cycle 6 phase dengan learning cycle 3 phase dan rata-rata penguasaan konsep termokimia dengan model learning cycle 6 phase lebih tinggi dibandingkan model learning cycle 3 phase. Hal ini karena model learning cycle 6 phase memiliki tahap-tahap lebih terperinci dalam meningkatkan penguasaan konsep termokimia. Kata kunci : model learning cycle 3 phase, model learning cycle 6 phase, penguasaan konsep.